A novel optical method to assess cervical changes during pregnancy and use to evaluate the effects of progestins on term and preterm labor - Kuon, Ruben-Jeremias; Shi, Shao-Qing; Maul, Holger; Sohn, Christof; Balducci, James; Shi, Leili; Garfield, Robert E. (American journal of obstetrics and gynecology, 2011)
Objective - The purpose of this study was to determine whether optical methods can estimate cervix function during pregnancy and whether progestins modify this process. - Study Design - Photos of the external cervix of timed-pregnant rats were taken every other day from day 13 until postpartum day 5 after daily treatments with vehicle (controls) or progestin treatments (progesterone, subcutaneously or vaginally; 17-alpha-hydroxyprogesterone caproate [17P] and RU-486 subcutaneously, once on day 16). The surface area of the cervix was estimated from photos. - Results - The surface area of cervix increases throughout pregnancy and reverses after delivery in controls. In the progesterone subcutaneously or 17P subcutaneously groups, increases in surface area are lower (17P group until day 19 only; P < .05). Vaginal progesterone does not prevent surface area increases. Only the progesterone subcutaneously blocked delivery. RU-486 increases the surface area of the cervix (P < .05) during preterm delivery. - Conclusion - An optical method is useful for quantitative assessment of the cervix and evaluation of agents that modify cervical function.
Gesehen am 11.07.2022